Urban design method: theory and practice: a case study in Malaysia - Sulaiman, Sulaiman (2001)
This research sets out to investigate methods to design urban spaces in Malaysia by studying the approach adopted by architects. The primary concern is the design of exterior spaces with the assumption that the poor urban spaces found in Malaysian urban areas is due to the weaknesses in the design method adopted by designers. For this purpose, the research addressed these objectives:- (1) To identify the reasons why the design of urban spaces is neglected by architects that produce poor continuity in the design of urban spaces, (2) To examine the process adopted and the infonnation used by architects in the design of urban ensemble and (3) To investigate the ways in which the architects responded to the needs of the user and the public.